A new Eastern Central Atlantic skate Raja parva sp. nov. (Rajoidei: Rajidae) belonging to the Raja miraletus species complex - Last, Peter R.; Séret, Bernard (Zootaxa, 2016)
An investigation of combined CO1 and NADH2 data for rajid skates referable to Raja miraletus provided evidence that populations ranging from southern Africa to the North-East Atlantic and Mediterranean Sea, once considered to represent a cline, belong to a species complex consisting of at least four valid species. Raja miraletus appears to be confined to the Mediterranean Sea, and the North-East Atlantic from the Bay of Biscay south to Morocco and Madeira. The southernmost species, referable to the resurrected Raja ocellifera, occurs off southern Africa, off Namibia and from False Bay to Durban (South Africa). Two species occur off tropical West Africa, including Raja parva sp. nov. (Senegal, Liberia and Angola but is probably more widespread within the region), and another unidentified species needing further investigation. Raja cf. miraletus, confirmed from Mauritania and Senegal, appears to be a larger skate with a broader disc, more broadly pointed snout, larger spiracles, and a slightly longer and broader tail. Raja parva sp. nov. differs from nominal members of the complex in having an unusually long procaudal tail (exceeding 22% TL), as well as a combination of other external characters. Past investigators observed morphological and anatomical differences between these forms but these were thought to be due to intraspecific variability. They postulated that an upwelling at Cape Blanco (21°N) may have isolated the Mediterranean form (R. miraletus) from Mauritania-Senegal form (now known to be two species). Similarly, the Benguela Current and upwelling off Cape Frio (18°S) were thought to be responsible for separating the Angolan form (R. parva) and South African form (R. ocellifera).